Molecular dynamics simulation study of the growth of a rough amorphous carbon film by the grazing incidence of energetic carbon atoms - Joe, Minwoong; Moon, Myoung-Woon; Oh, Jungsoo; Lee, Kyu-Hwan; Lee, Kwang-Ryeol (PERGAMON-ELSEVIER SCIENCE LTD, 2012)
The morphological evolution of an amorphous carbon film deposited by energetic carbon atoms of 75 eV with various angles of incidence was investigated by molecular dynamics simulation. Normal or near-normal incidence of carbon atoms resulted in a smooth surface of the deposited film. In contrast, a bump-like surface structure emerged and led to rough surfaces at grazing incidences, in agreement with the experiments. The bifurcated growth mode was explained by the impact-induced transport of atoms on the growing surface. The downhill transport of atoms on a sloping surface dominates at normal incidence, which suppresses the evolution of surface irregularities to form a rough surface. However, the dominance of uphill transport at a grazing incidence made the surface irregularities grow to a seed structure, which provided the shadowing effect during carbon deposition. This mechanism mediates initial seed formation and subsequent roughening together with shadowing effects under grazing incidence. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: GLANCING ANGLE DEPOSITION; THIN-FILMS; DIAMOND; MECHANISM